Numerical simulation of EPS geofoam behaviour in triaxial tests. Issue 5 (6th July 2015) - Ekanayake, Sanka Dilshan; Liyanapathirana, D.S.; Leo, Chin Jian
Abstract : Purpose: – EPS geofoam has been widely used in embankment construction, slope stabilisation, retaining walls, bridge approaches and abutments. Nevertheless, the potential of EPS geofoam as an engineering material in geotechnical applications has not been fully realised yet. The purpose of this paper is to present the finite element formulation of a constitutive model based on the hardening plasticity, which has the ability to simulate short-term behaviour of EPS geofoam, to predict the mechanical behaviour of EPS geofoam and it is implemented in the finite element programme ABAQUS. Design/methodology/approach: – Finite element formulation is presented based on the explicit integration scheme. Findings: – The finite element formulation is verified using triaxial test data found in the literature (Wong and Leo, 2006 and Chun et al., 2004) for two varieties of EPS geofoam. Performance of the constitute model is compared with four other models found in the literature and results confirm that the constitutive model used in this study has the ability to simulate the short-term EPS geofoam behaviour with sufficient accuracy. Research limitations/implications: – This research is focused only on the short-term behaviour of EPS geofoam. Experimental studies will be carried out in future to incorporate effects of temperature and creep on the material behaviour. Practical implications: – This formulation will be applicable to finite element analysis of boundary value problems involving EPS geofoam (e.g. application of EPS geofoam in ground vibration isolation, retaining structures as compressible inclusions and stabilisation of slopes). Originality/value: – Finite element analysis of EPS geofoam applications are available in the literature using elastic perfectly plastic constitutive models. However, this is the first paper presenting a finite element application utilising a constitutive model specifically developed for EPS geofoam.